Novi koronavirus - nove obveznosti delodajalca? - Majhenič, Zala (Pravni letopis, 2021)
The authors present employer`s liability for COVID-19 infection in the workplace. In particular they raise question of whether and under what conditions is the employer liable, what is the legal nature of this liability (strict, culpable liability), under which circumstances will the work classify as dangerous activity (due to the higher risk of exposure to COVID-19 infection). The authors also discuss, when has the worker right to refuse work, how and under what conditions is the employer discharged of liability and after all, what is the legally recognized damage caused by the COVID-19 infection, and how to reimburse it. The authors present their views through the prism of the current regulation of the Slovenian legal order, and the analysis, which also includes the current case law of Slovenian courts and the European Court of Human Rights.
Keywords: COVID-19; delodajalci; delovna mesta; delovno pravo; nevarnost; obligacijska razmerja; odškodninska odgovornost; odškodninsko pravo; varnostni ukrepi